Algal Cells-Derived Extracellular Vesicles: A Review With Special Emphasis on Their Antimicrobial Effects - Bayat, Fereshteh; Afshar, Alireza; Baghban, Neda (Frontiers in Microbiology, 2021)
Extracellular vesicles (EVs) originated from different cells of approximately all kinds of organisms, recently got more attention because of their potential in the treatment of diseases and reconstructive medicine. To date, lots of studies have been performed on mammalian-derived vesicles, but little attention has been paid to algae and marine cells as valuable sources of EVs. Proving the promising role of EVs in medicine requires sufficient resources to produce qualified microvesicles. Algae, same as its other sister groups such as plants, have stem cells and stem cell niches. Previous studies showed the EVs in plants and marine cells. So, this study was set out to talk about algal extracellular vesicles. EVs play a major role in cell-to-cell communication to convey molecules such as RNA/DNA, metabolites, proteins, and lipids within. The components of EVs depend on the origin of the primitive cells or tissues and the isolation method. Sufficient resources are needed to produce high-quality, stable, and compatible EVs as a drug or drug delivery system. Plant stem cells have great potential as a new controllable resource for the production of EVs. The EVs secreted from stem cells can easily be extracted from the cell culture medium and evaluated for medicinal uses. In this review, the aim is to introduce algae stem cells as well as EVs derived from algal cells. In the following, the production of the EVs¸the properties of EVs extracted from these sources and their antimicrobial effects will be discussed.